Interpreting the Wali Songo Da'wah through Punokawan: Schleiermacher's Hermeneutical Study - Nurrohmatillah, Iga; Kusumonagoro, Jupri Bandang Prawirodigdoyo; Hidayah, Luthfi; Assoburu, Selvia (International Journal of Islamic Thought and Humanities, 2024)
Da'wah puppet skin The Punokawan is preaching, culturally packaged​ in the form of a symbol through traditional arts. Wayang figures are believed to have been created by the Walisongo as a medium for Islamic preaching in Java. In understanding these symbols, Friedrich DE Schleiermacher's hermeneutic approach is used, emphasizing the importance of the relationship between the reader, author, and text. Schleiermacher argued that to understand a text in its entirety; one must explore the psychological aspects and position of the author. Therefore, in interpreting the form of Punokawan, especially the figure of Semar, an understanding of the social, cultural, and spiritual context of Walisongo at that time is needed. This study employs the systematic literature review method, incorporating Schleiermacher's intentional hermeneutic approach, and is supported by Roland Barthes' semiotic Theory as a tool for analyzing symbols and signs. The results of the study indicate that the interpretation of the Semar character has not been based entirely on the values of Islamic preaching, which are the basis of its creation. Thus, this study aims to provide a deeper understanding of the preaching message contained in Punokawan, a legacy of Walisongo's symbolic communication.